2011
DOI: 10.2967/jnumed.110.087114
|View full text |Cite
|
Sign up to set email alerts
|

Using the NEMA NU 4 PET Image Quality Phantom in Multipinhole Small-Animal SPECT

Abstract: Several commercial small-animal SPECT scanners using multipinhole collimation are presently available. However, generally accepted standards to characterize the performance of these scanners do not exist. Whereas for small-animal PET, the National Electrical Manufacturers Association (NEMA) NU 4 standards have been defined in 2008, such standards are still lacking for small-animal SPECT. In this study, the image quality parameters associated with the NEMA NU 4 image quality phantom were determined for a small-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 15 publications
5
22
0
Order By: Relevance
“…However, the number of iterations obtained in the present study may not be truly predictive for the number of iterations needed for a mouse or rat scan, which need some specific adjustments. All this is in line with the proposal of Harteveld et al (18) about the development of a NEMA NU 5 standard for SPECT and, more specifically, the use of an additional phantom with smaller internal structures and smaller outer diameter to better mimic mouse acquisitions such as the one proposed by Visser et al (23).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…However, the number of iterations obtained in the present study may not be truly predictive for the number of iterations needed for a mouse or rat scan, which need some specific adjustments. All this is in line with the proposal of Harteveld et al (18) about the development of a NEMA NU 5 standard for SPECT and, more specifically, the use of an additional phantom with smaller internal structures and smaller outer diameter to better mimic mouse acquisitions such as the one proposed by Visser et al (23).…”
Section: Discussionsupporting
confidence: 79%
“…We first observed that more iterations were required to reach convergence (and maximum RCs) for the smaller rods because high frequencies converge more slowly than low frequencies. Harteveld et al (18) reported the same observation for the U-SPECT-II using also the IQ phantom.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This phantom has been previously used for characterizing small-animal SPECT systems [2325]. The phantom has three different sections: a section with two cold cylinders with a hot background, a larger uniform cylinder filled with radiotracer, and a hot rod section with five different rod diameters (1, 2, 3, 4 and 5 mm).…”
Section: Methodsmentioning
confidence: 99%
“…3,[5][6][7][8][9] Recently, some authors have focused their attention on the quantification of system resolution as well as other quantitative parameters related to image quality, such as absolute quantification, [11][12][13] recovery coefficients (RC), and noise. 12,14 These studies characterize the image-quality parameters as a function of reconstruction settings and of the correction of attenuation and scatter in the object. The effect of the reconstruction algorithms on quantification has also been studied.…”
Section: Introductionmentioning
confidence: 99%